PENGARUH PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) TERHADAP HASIL BELAJAR PENJUMLAHAN PECAHAN - Hasnah, Nur; Ahmad, Syafri; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aims to determine the effect of Realistic Mathematics Learning approach (PMR) on student learning outcomes in the sum of fractions in class IV SD Negeri 13 Cingkariang District Banuhampu. The type of this research is experimental research with Quasi Exsperimental design. The sample in this research is class IVA and class IVB. Result of calculation of research data used is t-test with significant level 5% (0,05) obtained t arithmetic (22,67)> t table (1,67722). Thus it can be concluded that there is a significant influence between PMR approach to the result of fractional addition to fourth grade students of SD Negeri 13 Cingkariang.Keywords: PMR Approach, Sum of Fractions, Learning Outcomes.